substitution

posted by .

solve by the substitution method

3x+5y=21
x=51-9y

  • substitution -

    Substitute 51 -9y for x in the first equation and solve for y. Put that value in the second equation to find x. Check by putting both values into the first equation.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Substitution Method

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 x + y = -4 x - y = 2 In the second equation, x= y+2 Putting that in the first.. (y+2) + y= -4 subtract two from each side, then divide each side by …
  2. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
  3. Linear Equations

    Can you please help solve this equation using the substitution method?
  4. math substitution method

    use the substitution method to solve 7x+5y=-26 x=28-6y
  5. substitution

    solve by the substitution method 3x+5y=21 x=51-9y
  6. substitution method

    Solve by substitution method please help me solve this. I do not know how to do this at all. The question is 3x+8y=33 and x=31-6y I know that I have to plug x into the first x like 3(31-6y)+ 8y = 33 but i do not know what to do from …
  7. algebra

    use the Substitution Method. Please give it a try. y = 3x + 4 5x + 3y = 12 Why is the substitution method preferred in this case?
  8. Algerbra 1 substitution method

    im really confused about this question: 2x-3y=21 y=3-x using substitution method. please help
  9. Algebra 1

    bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
  10. Math

    17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.

More Similar Questions